2018
DOI: 10.1080/21632324.2018.1463903
|View full text |Cite
|
Sign up to set email alerts
|

Migration and multidimensional well-being in Ethiopia: investigating the role of migrants destinations

Abstract: The purpose of this paper is to better understand the relationship between migration and multi-dimensional well-being in the context of Ethiopia. We investigate the differences in well-being between migrant, non-migrant and return migrant households. We then go a step further to understand the role of migrants destinations for well-being by disaggregating migration destination to the Middle East, Africa and the North. We find that migrant and return migrant households are better off in terms of well-being than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Communities with better education and social infrastructures are unlikely to send its members into migration because such communities have the basic needs that individuals who want to migrate would look for. Further, Kuschminder, Andersson, and Seigel (2018) also found that in education dimension, migrant household are significantly less likely to be better off than non-migrant households and as a result, the urge to migrate is reduced even at a community level as there is a wider market for individuals to even pursue their own opportunities locally.…”
Section: Random Effects Probit Model Resultsmentioning
confidence: 96%
“…Communities with better education and social infrastructures are unlikely to send its members into migration because such communities have the basic needs that individuals who want to migrate would look for. Further, Kuschminder, Andersson, and Seigel (2018) also found that in education dimension, migrant household are significantly less likely to be better off than non-migrant households and as a result, the urge to migrate is reduced even at a community level as there is a wider market for individuals to even pursue their own opportunities locally.…”
Section: Random Effects Probit Model Resultsmentioning
confidence: 96%
“…Nonmigrants may have a lower baseline level of wellbeing because of the lack of resources to migrate (Brockerhoff, 1995; Kulu, 2005). These resources include not only financial resources but also social contacts in urban areas, which would facilitate the diffusion of fertility preferences (Kuschminder, Andersson, & Seigel, 2018). Finally, the disruption perspective suggests that immediately after migration, social networks are dislocated, and fertility may be temporarily reduced with reduction in social control, which can increase the use of family planning (Kulu, 2005; Majelantle, 2014).…”
Section: Theoretical Framework For Fertility Behaviourmentioning
confidence: 99%
“…In addition, studies done by Abdelatti, Elhadary, and Babiker (2017); Abou-Korin and Al-Shihri (2015); Khraif, Salam, Elsegaey, Aldosari, and Al-Mutairi (2015), Khraif et al (2016);and Bassam (2011), have discovered that Arab countries-in particular Saudi Arabia, Bahrain and the United Arab Emirates-have undergone drastic urbanisation as a result of migration especially from immigrants who came to the countries as labourers in construction, the service industry, and also domestic work. Kuschminder et al (2018) have provided a further discussion on this scenario. This migration, furthermore, had a significant impact on demographic changes like gender, age, structure and social changes, including changing lifestyles as a result of urbanism and assimilation.…”
Section: Migration and Urban Systemsmentioning
confidence: 97%
“…Many migration theories, especially classical theories -also known as economic migration models, like Ravenstein, Lewis, and Todaromodels (see discussions in De Vries, Nijkamp, & Rietveld, 2000;Neto & Mullet, 1998)-recognise migration as sending labours to urban areas for industrial sectors, and the effects have been encouraging urban growth, as the high volume of migration increases demands for housing, infrastructure and basic urban services. This situation has attracted psychologists to also give attention to migration studies from the aspect of new culture adaptation and ethnic relations (Berry, 2001;Cuervo & Hin, 1998), in addition to other main fields that are directly connected to migration studies like anthropology, sociology, economy, and urban planning and development (Berry, 2001;Willis, 2010;Kuschminder, Andersson, and Seigel (2018). This is because the migration interaction (behaviour) on the urban system creates many issues in urban areas, whether positive or negative, that are related to the scope of urbanisation, demographic changes and social aspects of a population.…”
Section: Migration and Urban Systemsmentioning
confidence: 99%